Advancing industrial marketing theory: The need for improved research - Peter LaPlaca (jbm - Journal of Business Market Management, 2014)
Industrial Marketing Management was the first journal devoted exclusively to advancing the science of industrial or business-to-business marketing. Prior to its launch in 1972, fewer than five percent of all articles published in marketing journals focused on industrial marketing1 while over half of the GDP in industrialized economies was due to B2B activities. Consumer marketing dominated academic research. With a new outlet for B2B research, the percentage of articles focusing on industrial marketing increased to 20 percent.
urn:nbn:de:0114-jbm-v7i1.840
Keywords: 650